2019
DOI: 10.1091/mbc.e19-03-0166
|View full text |Cite
|
Sign up to set email alerts
|

The mitochondrial intermembrane space–facing proteins Mcp2 and Tgl2 are involved in yeast lipid metabolism

Abstract: Mitochondria are unique organelles harboring two distinct membranes, the mitochondrial inner and outer membrane (MIM and MOM, respectively). Mitochondria comprise only a subset of metabolic pathways for the synthesis of membrane lipids; therefore most lipid species and their precursors have to be imported from other cellular compartments. One such import process is mediated by the ER mitochondria encounter structure (ERMES) complex. Both mitochondrial membranes surround the hydrophilic intermembrane space (IMS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 67 publications
3
14
0
Order By: Relevance
“…Moreover, Cqd2 was previously identified as a high-copy suppressor of a growth defect caused by loss of the ERMES subunit Mdm10 21 . More recently, three conserved Cqd2 active site residues were shown to mitigate rescue of Δmdm10 yeast growth 22 , results that we confirm (Cqd2 K210R) and expand upon with six additional residue mutations. Interestingly, mitochondrial CoQ export still occurs in the absence of Cqd1/2, indicating that additional factors can participate in this process.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Moreover, Cqd2 was previously identified as a high-copy suppressor of a growth defect caused by loss of the ERMES subunit Mdm10 21 . More recently, three conserved Cqd2 active site residues were shown to mitigate rescue of Δmdm10 yeast growth 22 , results that we confirm (Cqd2 K210R) and expand upon with six additional residue mutations. Interestingly, mitochondrial CoQ export still occurs in the absence of Cqd1/2, indicating that additional factors can participate in this process.…”
Section: Discussionsupporting
confidence: 80%
“…1b). Previous studies have identified genetic and physical interactions connecting Cqd2 to mitochondrial lipid homeostasis, but not to a specific pathway [21][22][23] . Given the similarity between these three proteins (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we asked whether the protein kinase-like domain of Cqd1 is important for its function. We generated mutants in conserved amino acid residues within this domain (K275A, D288A and E330A) to inhibit ATP binding similar to what was done before in studies on Cqd2 and Coq8 (Odendall et al, 2019; Reidenbach et al, 2018; Stefely et al, 2015). Of note, introduction of the point mutations K275A or D288A led to strongly reduced steady state levels of Cqd1 indicating reduced expression or stability of the protein (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Members of the poorly characterized UbiB protein kinase-like family (aarF domain containing kinases) were recently implicated in mitochondrial membrane homeostasis (Awad et al, 2020; Johnson et al, 2005; Kemmerer et al, 2021; Mollet et al, 2008; Odendall et al, 2019; Reidenbach et al, 2018; Stefely et al, 2015). UbiB family members are defined by the presence of a protein kinase-like domain (PKL) of unknown function.…”
Section: Introductionmentioning
confidence: 99%
“…The deficiency of MFN1 and MFN2 leads to reduced mitochondrial fusion [55] . In addition, MFN2 controls cellular apoptosis and mitochondrial autophagy [56] . OPA1, a mitochondrial fusion protein, may also play a role as mitophagic factors.…”
Section: Mitochondrial Fusion Proteinsmentioning
confidence: 99%